Tawhid, Worship, and Noble Morals in the Hikayat Nabi Isa - Saefullah, Muhammad Iqbal; Wirajaya, Asep Yudha (Buletin Al-Turas, 2024)
PurposeThe main objective of this research was to reveal the Islamic teachings in the Hikayat Nabi Isa manuscript. MethodThis qualitative study employed a descriptive research design. The philological method used was the legger method. Content analysis in this study uses textual and contextual analysis. The primary data source was the manuscript of Hikayat Nabi Isa (hereinafter referred to as HNI) in the collection of the French National Library with the code Malayo-Polynesien 68. The research data was collected using reading and note writing technique. Results/findingsThis study revealed the Islamic teachings that the HNI text demonstrated encompassed tawhid (aqidah), worship (sharia), and noble morals (akhlaqul karimah). Conclusion The HNI manuscript was a highly readable manuscript that was well-preserved and easily accessible. The HNI text narrated the history of Prophet Isa and conveyed the Islamic teachings, which included the teachings of aqidah, sharia, and morals.